Protease Inhibitors Extracted from Caesalpinia echinata Lam. Affect Kinin Release during Lung Inflammation - Cruz-Silva, Ilana; Nunes, Viviane Abreu; Gozzo, Andrezza Justino; Praxedes-Garcia, Priscila; Tanaka, Aparecida Sadae; Shimamoto, Kazuaki; Araujo, Mariana Silva (Pulmonary Medicine, 2016)
Inflammation is an essential process in many pulmonary diseases in which kinins are generated by protease action on kininogen, a phenomenon that is blocked by protease inhibitors. We evaluated kinin release in an in vivo lung inflammation model in rats, in the presence or absence of CeKI (C. echinata kallikrein inhibitor), a plasma kallikrein, cathepsin G, and proteinase-3 inhibitor, and rCeEI (recombinant C. echinata elastase inhibitor), which inhibits these proteases and also neutrophil elastase. Wistar rats were intravenously treated with buffer (negative control) or inhibitors and, subsequently, lipopolysaccharide was injected into their lungs. Blood, bronchoalveolar lavage fluid (BALF), and lung tissue were collected. In plasma, kinin release was higher in the LPS-treated animals in comparison to CeKI or rCeEI groups. rCeEI-treated animals presented less kinin than CeKI-treated group. Our data suggest that kinins play a pivotal role in lung inflammation and may be generated by different enzymes; however, neutrophil elastase seems to be the most important in the lung tissue context. These results open perspectives for a better understanding of biological process where neutrophil enzymes participate and indicate these plant inhibitors and their recombinant correlates for therapeutic trials involving pulmonary diseases.